Biosynthesis and chemical characterization of polydopamine‐capped silver nanoparticles for the treatment of acute myeloid leukemia in comparison to doxorubicin in a leukemic mouse model. (3rd December 2019) - Hemmati, Saba; Joshani, Zeinab; Zangeneh, Akram; Zangeneh, Mohammad Mahdi
Abstract : The recent study reveals the cytotoxicity, antioxidant, and anti‐acute myeloid leukemia properties of polydopamine (PDA)‐capped silver nanoparticles (AgNPs) compared to doxorubicin in a leukemic mouse model. The synthesized AgNPs were characterized using different techniques including ultraviolet–visible spectroscopy (UV–Vis.), Fourier‐transform infrared spectroscopy (FT‐IR) spectroscopy, X‐ray diffraction (XRD), energy Dispersive X‐ray Spectrometry (EDS), field emission‐scanning electron microscopy (FE‐SEM), and transmission electron microscopy (TEM). FE‐SEM and TEM images revealed a uniform spherical morphology and average diameters of 15–25 nm for the nanoparticles. Also, in XRD analysis, 20 nm was measured for the crystal size of nanoparticles. The results of the biological experiments were fed into SPSS‐22 software and analyzed by one‐way ANOVA. In the biological in vitro part of this study, AgNPs similar to doxorubicin had low cell viability dose‐dependently against Human HL‐60/vcr, 32D‐FLT3‐ITD, and Murine C1498 cell lines without any cytotoxicity on HUVEC cell line. In this study, 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) test revealed similar antioxidant potentials for doxorubicin and AgNPs. In the biological in vivo part of this study, induction of acute myeloid leukemia was done by 7, 12‐Dimethylbenz[a]anthracene (DMBA) in 75 mice. Then, the animals were randomly divided into six subgroups, including control, untreated, doxorubicin, AgNPs, PDA, and AgNO3 . AgNPs similar to doxorubicin, significantly ( p ≤ 0.05) reduced the pro‐inflammatory cytokines, and the total white blood cell (WBC), blast, monocyte, neutrophil, eosinophil, and basophil counts and enhanced the anti‐inflammatory cytokines and the platelet, lymphocyte, and red blood cell (RBC) parameters as compared to the untreated mice. By quantitative real‐time polymerase chain reaction (PCR), sphingosine‐1‐phosphate receptor‐1 (S1PR1) and sphingosine‐1‐phosphate receptor‐5 (S1PR5) mRNA expression in lymphocytes were significantly ( p ≤ 0.05) raised by treating the leukemic mice with the AgNPs and doxorubicin. Above results confirm the therapeutic effects of AgNPs on acute myeloid leukemia in the leukemic mice. Further clinical trials are necessary for confirmation these remedial properties of AgNPs in human. Abstract : The cytotoxicity, antioxidant, and anti‐acute myeloid leukemia properties of polydopamine (PDA)‐capped silver nanoparticles (AgNPs)were studied.